Dietary supplementation of Cannabis sativa residues in broiler chickens affects performance, carcass characteristics, intestinal morphology, blood biochemistry profile and oxidative stability - Yusup Sopian; Apinya Sartsook; Chaiwat Arjin; Chompunut Lumsangkul; Korawan Sringarm; Panneepa Sivapirunthep; Chanporn Chaosap (My University, 2024)
Public interest in the cannabis plant has increased after its legalization in many countries. Cannabis sativa residues (CR) are a part of the plant waste in the cannabis industry. The CR contain medicinal properties that could be used as a feed additive in poultry production. The trial was conducted to investigate the effects of CR on growth performance, carcass characteristics, intestinal morphology, and blood biochemistry profile of broiler chickens. In a completely randomized design, 256 one-day-old male Ross 308 broilers were randomly allocated to 4 treatments with 8 replicates and 8 birds per replicate. These 4 dietary treatments included a basal diet with 0, 0.5, 1 and 2% CR for 40 d. The results showed that 2% CR supplementation reduced feed intake (FI) in the starter phase (d 3-23, P < 0.05). The birds in the CR groups had lower FI in the finishing phase (d 24-40, P < 0.01) and the whole raising period (d 3-40, P < 0.01) than the control. However, the body weight and carcass yield were not different (P > 0.05). In addition, the CR diet had no adverse effects on the blood biochemistry profile, including total cholesterol, triglycerides, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total protein, globulin, albumin, and direct bilirubin (P > 0.05). In addition, total bilirubin and malondialdehyde were better in the plasma of CR-supplemented birds than in the control groups (P < 0.05). The observations on intestinal morphology showed that CR supplementation improved the ratio between villus height and crypt depth in the ileum (P < 0.05). In conclusion, CR supplementation can improve intestinal morphology and oxidative stability of broiler chickens. This suggests that CR could potentially be used as an alternative feed additive in broiler production.
Keywords: Gizzard; Malondialdehyde; Cannabis and Cannabinoid Research